Quality Assessment of Antibiotic Oral Drug Formulations Marketed In Katsina State, Nigeria - Lawal, Mukhtar Gambo; Mukhtar, Muhammad Dauda; Magashi, Abdulkadir Magaji (Asian Journal of Pharmaceutical Research and Development, 2019)
There are increasing reports on the high incidence of substandard drugs, especially in developing countries.Pharmaceutical products have been reported to contain either no, low, or excessive amounts of the active pharmaceutical ingredient (API). Inview of the above, 112 samples of six different antibiotic oral drug formulations were evaluated for chemical quality by assessing the presence and the percentage content of the stated active pharmaceutical ingredients using validated HPLC assay as described in the official monograph of the British and United Stated pharmacopoeia. The result indicates that 43 (38.4%) had active ingredients outside the set pharmacopoeial limit and therefore were non-compliant to the BP and the USP specifications for percentage content. Ampiclox and Cotrimoxazole had the highest proportion of samples with active ingredient outside the pharmacopoeial limit, and in three samples (one Augmentin and two Ampiclox), no active ingredient was detected. The presence of API lower than the claimed content declared on the packaging was the primary cause of non-compliance. The potential implications of the use of substandard drugs are treatment failure and the development of drug-resistance.